AI Literacy and the Changing Digital Political Landscape - Elizabeth Losh; Rita Raley; Delores B. Phillips; Reed Van Schenck; Stefania Milan (Lateral)
Delores Phillips and Cultural Studies Association’s New Media and Digital Cultures Working Group Co-Host Reed Van Schenck discuss AI literacy, digital politics, and the 2024 US presidential election with authors Elizabeth Losh (William and Mary) and Rita Raley (UC Santa Barbara). This podcast is accompanied by a scholarly commentary by Stefania Milan.